West Side Story: systematics of funnel-weavers (Araneae: Agelenidae: Ageleninae) from arid western South Africa, with two new genera and 16 new species - Haddad, Charles R.; Zamani, Alireza; Marusik, Yuri M. (Zootaxa, 2026)
In this study, we document the diversity of funnel-weaving spiders (Agelenidae: Ageleninae) in arid western South Africa, a fauna that has historically been understudied. Examination of collected material revealed 16 new species belonging to two tribes, Textricini and Agelenini, representing three genera, including two newly described herein. Afrotrix gen. nov. (Textricini) is described to comprise A. deserticola (Simon, 1910) comb. nov. (ex. Benoitia Lehtinen, 1967), for which a lectotype is newly designated, as well as nine new species: A. spicula sp. nov. (type species, ♂♀), A. booyseni sp. nov. (♂♀), A. dejagerae sp. nov. (♂♀), A. goegap sp. nov. (♀), A. karooica sp. nov. (♂♀), A. lyonsae sp. nov. (♂♀), A. reginaldi sp. nov. (♂♀), A. sauria sp. nov. (♀) and A. tankwa sp. nov. (♂♀). Benoitia Lehtinen, 1967 (Agelenini) is represented by the following five new species: B. arida sp. nov. (♀), B. leroyae sp. nov. (♀), B. lunata sp. nov. (♀), B. meridionalis sp. nov. (♂♀) and B. namaqua sp. nov. (♂♀). Finally, Namagelena gen. nov. (Agelenini) is described to comprise two new species, N. sola sp. nov. (type species, ♂♀) and N. guttata sp. nov. (♀). A molecular phylogeny is presented based on cytochrome c oxidase subunit I (COI) sequences of 12 species of South African Agelenidae, including 10 described in this paper, which supports the delimitation of the three genera treated. Distribution maps are provided for all the species.